Oral signs in juvenile dermatomyositis - Dourado, Mauricio Rocha; Silva Filho, Tiago Joao da; Salo, Tuula (Journal of Oral Diagnosis, 2017)
Juvenile Dermatomyositis (JDM) is a severe inflammatory myopathy characterized by multisystemic vasculopathy during childhood. The general profile consists of symmetric proximal muscle weakness and the presence of characteristic rashes. This case describes an 11-year-old girl with hyperplastic gingival inflammation, telangiectasia and lichenoid retroalveolar striae detected by dental examination visit, when she also showed rash and papules in her hands. Histopathological diagnosis of the retroalveolar mucosa was indica- tive of unspecific chronic inflammation. Later when muscle symptoms and serum changes were present the JDM diagnosis was confirmed. The patient was successfully treated with systemic corticosteroids and regular professional dental cleaning. In order to get an early diagnosis and effective treatment for the patients, it is important that oral health care providers are aware of the oral manifestations related to systemic diseases, such as JDM.